Discourse on the Best Interpretation Model: A Critical Review of Traditional Exegesis Products in the Early Era - Mahdi Afandi; Abd. Kholid; Mursyid, Achmad Yafik (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
In addition to interpreting the Qur'an through rational reasoning (ra'yi), scholars also employ an interpretive approach based on narrations, known as the bi al-ma’thūr interpretation. This form of interpretation is esteemed by Ibn Taimiyah and Ibn Kathir and carries high validity and evidential support. To such an extent, outcomes from the bi al-ma'ṡur interpretation are obligatory and not to be disregarded. This study critically analyzes and validates the bi al-ma’thūr interpretation model that emerged in the mutaqaddimīn era. The focus is on two seminal interpretations, namely